2015
DOI: 10.1902/jop.2015.150278
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide and Sitagliptin Decrease Interleukin 1β, Matrix Metalloproteinase 9, and Nitric Oxide Synthase 2 Gene Expression But Does Not Reduce Alveolar Bone Loss in Rats With Periodontitis

Abstract: Regardless of the reduction of the expression of Il1b, Nos2, and Mmp9, the drugs were not effective in the stabilization or reduction of alveolar bone loss and collagen degradation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Recent study showed that inhibition of CD 26 signaling inhibited human osteoclast development and humanized anti-CD26 monoclonal antibody may have therapeutic potential for the treatment of osteolytic lesions [33]. Recently some studies reported that DPP4i had anti-inflammatory effects and it also becomes the another possibility [34,35]. And increased levels of GIP might be able to affect the result though we did not measure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that inhibition of CD 26 signaling inhibited human osteoclast development and humanized anti-CD26 monoclonal antibody may have therapeutic potential for the treatment of osteolytic lesions [33]. Recently some studies reported that DPP4i had anti-inflammatory effects and it also becomes the another possibility [34,35]. And increased levels of GIP might be able to affect the result though we did not measure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that severe periodontitis has been associated with a robust increase in plasma TG (Maekawa et al 2011 ; D’Aiuto et al 2006 ), which is agreed by the present study. NSPT improved plasma lipid, which might be another mechanism by which NSPT decreased inflammatory response in the arterial wall (Moraes et al 2015 ; Cho 2002 ; Lemaitre et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…without effect on alveolar bone loss in periodontally affected rats 114. Intensified metabolic treatment with glycated hemoglobin reduction resulted in an improved inflammation state, characterized by decreased levels of C-reactive protein 115.…”
mentioning
confidence: 96%